2015
DOI: 10.1080/10871209.2015.1004144
|View full text |Cite
|
Sign up to set email alerts
|

Human–Wildlife Conflict 10 Years Later: Lessons Learned and Their Application to Cheetah Conservation

Abstract: Cheetah (Acinonyx jubatus) conservation is interconnected to social, economic, and environmental factors. Since the 2003 World Parks Congress, cheetah conservation practitioners have been applying human -wildlife conflict resolution strategies throughout Sub-Saharan Africa. Future Farmers of Africa training has taught farm management skills to over 3,000 rural Namibian farmers and is being used in other range countries. Capacity building for conservation scientists and extension officers has been conducted usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…Attempts to understand the behavior of damage-causing predators determine the most effective methods for reducing attacks (such as guarding livestock or providing safe water-collection points to avoid crocodile attacks), and educate local communities about employing methods to reduce their vulnerability have had some success (e.g., Balme et al 2009;Marker & Boast 2015). However, such interventions have also foundered in many places for a range of reasons, including failure to involve local people, high opportunity costs of effective livestock protection methods, and resistance to perceived infringements on freedom of behavior (Barua et al 2013), or as a result of epistemological disagreements over what causes predator attacks (Wallace et al 2011;Pooley 2016).…”
Section: Current Approaches To Human-predator Conflict Mitigationmentioning
confidence: 99%
“…Attempts to understand the behavior of damage-causing predators determine the most effective methods for reducing attacks (such as guarding livestock or providing safe water-collection points to avoid crocodile attacks), and educate local communities about employing methods to reduce their vulnerability have had some success (e.g., Balme et al 2009;Marker & Boast 2015). However, such interventions have also foundered in many places for a range of reasons, including failure to involve local people, high opportunity costs of effective livestock protection methods, and resistance to perceived infringements on freedom of behavior (Barua et al 2013), or as a result of epistemological disagreements over what causes predator attacks (Wallace et al 2011;Pooley 2016).…”
Section: Current Approaches To Human-predator Conflict Mitigationmentioning
confidence: 99%
“…Some of these incentives are employed in Namibia (Marker & Boast, 2015), but it is not clear what the public attitudes are towards these incentives. The second objective determined how financial incentives for carnivore conservation were framed in the national media.…”
Section: Thesis Objectivesmentioning
confidence: 99%
“…Financial mechanisms, such as compensation or income from tourism, have been suggested as a way to improve tolerance towards carnivores (Marker & Boast, 2015;Nelson et al, 2010;Stein et al, 2010) but some research has suggested that these methods are fraught with challenges, as the costs of wildlife presence still sometimes outweigh benefits, payments can be delayed (Kasaona, 2006) and the schemes can suffer from unequal benefit distribution (Rust & Marker, 2014) 6 . It therefore remains unknown as to what techniques are most effective and acceptable for improving carnivore coexistence on Namibian farms.…”
Section: Conserving Carnivores In Namibiamentioning
confidence: 99%
See 2 more Smart Citations